Scientific opinion on the evaluation of authorised ferric sodium EDTA as an ingredient in the context of Regulation (EC) 258/97 on novel foods and Regulation (EU) 609/2013 on food intended for infants and young children, food for special medical purposes and total diet replacement for weight control. (3rd August 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present opinion deals with the evaluation of the proposed increase of the currently authorised maximum amounts of ferric sodium ethylenediaminetetraacetic acid (EDTA) as a novel food ingredient used as a source of iron, and its extension of use in processed cereal‐based foods and baby foods. The applicant also provided information on two forms of ferric sodium EDTA, one previously assessed by EFSA and a new one of finer consistency. To support the proposed changes to the uses of ferric sodium EDTA, the applicant proposed a revision of the current acceptable daily intake (ADI) for EDTA, derived from that set for the food additive calcium disodium EDTA (E 385). The Panel confirmed that ferric sodium EDTA is a source from which iron is bioavailable. In assessing the safety of the proposed revision to the existing specifications for the novel food ingredient ferric sodium EDTA, the Panel noted that this would not discriminate between the previously evaluated substance and the one of finer consistency. In particular, the Panel noted that particle size was not one of the proposed parameters for the revised specifications. The Panel noted that it was not possible to determine whether particles of ferric sodium EDTA in the nano range were present in the product with finer consistency in the solid form. The toxicological data submitted did not add any new relevant information to the database on which the current ADI for EDTA is based. Consequently, the Panel concluded that there was no sound scientific justification to increase the ADI for EDTA and hence increase the use levels of ferric sodium EDTA or introduce additional uses as proposed by the applicant. The Panel recommended that additional toxicological data should be provided to address the shortcomings in the available toxicity database prior to the re‐evaluation of calcium disodium EDTA (E 385).